Structure of the DMPC lipid bilayer ripple phase - Akabori, Kiyotaka (Soft Matter, 2015)
High resolution structure is presented for the ripple (P(β′)) phase of the phospholipid dimyristoylphosphatidylcholine. Low angle X-ray scattering from oriented samples yielded 57 orders, more than twice as many as recorded previously. The determined electron density map has a sawtooth profile similar to the result from lower resolution data, but the features are sharper allowing better estimates for the modulated bilayer profile and the distribution of headgroups along the aqueous interface. Analysis of high resolution wide angle X-ray data shows that the hydrocarbon chains in the longer, major side of the asymmetric sawtooth are packed similarly to the L(βF) gel phase, with chains in both monolayers coupled and tilted by 18° in the same direction. The absence of Bragg rods that could be associated with the minor side is consistent with disordered chains, as often suggested in the literature. However, the new high resolution bilayer profile strongly suggests that the chains in the two monolayers in the minor side and the curved region are not in registry. This staggered monolayer modulated melting suggests a direction for improving theories of the ripple phase.